2016
DOI: 10.1002/etc.3614
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of lake sturgeon (Acipenser fulvescens) early life stages to 2,3,7,8‐tetrachlorodibenzo‐P‐dioxin and 3,3′,4,4′,5‐pentachlorobiphenyl

Abstract: The aquatic food web of the Great Lakes has been contaminated with polychlorinated biphenyls (PCBs) since the mid-20th century. Threats of PCB exposures to long-lived species of fish, such as lake sturgeon (Acipenser fulvescens), have been uncertain because of a lack of information on the relative sensitivity of the species. The objective of the present study was to evaluate the sensitivity of early-life stage lake sturgeon to 3,3',4,4',5-pentachlorobiphenyl (PCB-126) or 2,3,7,8-tetrachlorodibenzo-p-dioxin (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Median in ovo lethal dose (LD50) to 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin in common snapping turtle (present study indicated with an arrow) compared with species of birds (light gray) and fish (dark gray) that have been investigated. LD50 values are as reported previously (Buckler et al, 2015; Cohen‐Barnhouse et al, 2011a; Elonen et al, 1998; Park et al, 2014; Powell et al, 1998; Tillitt et al, 2017; Toomey et al, 2001; Walker et al, 1992; Walker & Peterson, 1994; Yamauchi et al, 2006). …”
Section: Discussionsupporting
confidence: 57%
“…Median in ovo lethal dose (LD50) to 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin in common snapping turtle (present study indicated with an arrow) compared with species of birds (light gray) and fish (dark gray) that have been investigated. LD50 values are as reported previously (Buckler et al, 2015; Cohen‐Barnhouse et al, 2011a; Elonen et al, 1998; Park et al, 2014; Powell et al, 1998; Tillitt et al, 2017; Toomey et al, 2001; Walker et al, 1992; Walker & Peterson, 1994; Yamauchi et al, 2006). …”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, high quality nursery habitats exist in downstream reaches of this system (Daugherty et al, 2009), and were used long‐term by acoustically tagged young‐of‐year Lake Sturgeon (Tucker, 2020), satisfying “settle and establishment” phases. In addition, habitat remediation (e.g., PCB removal, dredging, and capping) is ongoing throughout the LFR and Lower Green Bay (e.g., Cat Island Restoration) and is expected to improve river conditions and habitats for fish and wildlife (see Tillitt et al, 2017), including Lake Sturgeon. This research suggests the “spawn phase” for Lake Sturgeon below De Pere Dam may be hindered by poor incubation conditions (i.e., desiccation, retention, algae, and predation), subsequently resulting in a poor “drift phase”.…”
Section: Discussionmentioning
confidence: 99%
“…Dose–response curves for early life stage mortality that were predicted using EC Threshold or EC50 as input variable in the corresponding qAOPs were validated against 25 experimental dose–response curves from the published literature that reported measured concentrations and percentage of mortality for each dose (Brunstrom and Reutergardh 1986; Brunstrom and Lund 1988; Brunstrom 1989, 1990; Spitsbergen et al 1991; Walker et al 1994; Walker and Peterson 1994; Powell et al 1996, 1998; Elonen et al 1998; Hoffman et al 1998; Cohen‐Barnhouse et al 2011; Eng et al 2014, 2017; Tillitt et al 2017). These 25 scenarios represent 9 species of birds, 7 species of fish, and 5 different DLCs.…”
Section: Methodsmentioning
confidence: 99%